English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

can someone please explain to me how 27^(2/21) becomes 9^(1/7). I'm so confused and the textbook does not have an example like this, only simpler ones. A walkthrough would be greatly appreciated.

2007-03-04 05:50:14 · 6 answers · asked by Harry W 2 in Science & Mathematics Mathematics

6 answers

27 = 3^3 (3 cubed).
27^(2/21) = 3^(3*2/21) = 3^(2/7) = (3^2)^(1/7) = 9^(1/7).
Hope that's clear.

2007-03-04 05:59:46 · answer #1 · answered by Anonymous · 0 0

27^(2/21)=3^3^(2/21) and a^m^n=a^m*n

=3^3*2/21

=3^2(1/7)

=9^(1/7)

2007-03-04 14:02:17 · answer #2 · answered by psk 1 · 0 0

27 ^ ( 2/21) = (3 ^3) ^ (2/21) = 3 ^ (3 * 2/21) = 3^(2/7) = (3^2)^(1/7) = 9^(1/7)

2007-03-04 13:55:54 · answer #3 · answered by hustolemyname 6 · 0 0

27 = 3^3, so

27^(2/21) = (3^3)^(2/21) (switch the 3 and 2 by rules of exponents)

= (3^2)^(3/21) = 9^(1/7)

2007-03-04 13:55:38 · answer #4 · answered by Anonymous · 0 0

27^(2/21)
= (3^3)^(2/21)
= 3^(2/7)
= (3^2)^(1/7)
= 9^(1/7)

2007-03-04 13:57:38 · answer #5 · answered by sahsjing 7 · 0 0

27^(2/21) = 27^(2/3 * 1/7) = (27^(2/3))^(1/7)

This is the cube root of 27 squared to the one-seventh.

The cube root of 27 is 3, and 3 squared is 9.

Hence, 9^(1/7)

2007-03-04 13:55:15 · answer #6 · answered by Dave 6 · 0 0

fedest.com, questions and answers